Pengaruh Konsentrasi Asap Cair Terhadap Mutu Pengawetan Ikan Kembung Lelaki - Ni Made Darmadi; Monthanus Darisman Daba; I Gede Suryana Pandit (Fakultas Pertanian, Universitas Warmadewa, 2022)
This study aims to determine the effect of liquid smoke concentration on the chemical and organoleptic composition of male mackerel with 1 day immersion. This research was conducted in August 2021 at the Processing Laboratory of the Faculty of Agriculture, Warmadewa University. The research method used is an experimental method and the design used is a completely randomized design (CRD) with a single factor in the form of adding liquid smoke preservatives, adding liquid smoke preservatives which consists of 4 treatments and 3 replications, namely 25% liquid smoke soaking 1 day, 30% liquid smoke soaking for 1 day, and 35% liquid smoke soaking for 1 day. Observations were in the form of chemical analysis and microbial analysis, namely, protein, water content, and total PLATE count. The best analysis results were obtained with liquid smoke preservative at a concentration of 35%, water content 78.69%, total PLATE count 2.5x102 coloni/g, protein content 15.12, appearance 8.55, odor 8.33, taste 8.33 and texture 8.11